IMPLEMENTASI SURAT EDARAN MENTERI KETENAGAKERJAAN NO.M/3/HK.04/III/2020 DALAM MELINDUNGI KELANGSUNGAN HIDUP BURUH DAN PELAKU USAHA PADA MASA PANDEMI COVID-19 - Otong Syuhada; Aji Halim Rahman (Universitas Majalengka, 2022)
The economic crisis triggered by the COVID-19 pandemic has an impact on the employment situation in Indonesia. Seeing this situation, the Central Government through its policies made several efforts to deal with this problem. One form of government policy through the Minister of Manpower issued a Circular Letter of the Minister of Manpower No.M/3/HK.04/III/2020 concerning Protection of Workers/Labourers and Business Continuity in the Context of Prevention and Control of Covid-19, but almost all business actors or companies in responding to the government's policy by limiting social activities, including many companies that have taken the policy to lay off and cut wages for their workers/employees. The research method used is a research specification that is descriptive analytical using a Sociological Juridical Research approach. The research stage is through research that uses primary data and secondary data. Data collection techniques are document studies and interviews. The data collection tool uses library data and field data. In accordance with the approach method applied, the data obtained for this study were analyzed in a qualitative juridical manner. deductions from the wages of workers/laborers by employers and finally wage cuts can be made through the agreement of both parties due to the spread of the covid-19 virus as regulated based on the Circular Letter of the Minister of Manpower of the Republic of Indonesia Number M/3/Hk.04/III/2020. In resolving the issue of unilaterally cutting wages, it can be done by means of Bipartite and Tripartite. However, the recommendations issued by the labor agency mediator in this case do not have coercive power for the parties to carry out.